Evaluasi Unjuk Kerja Isolator 6 kV pada Gardu Distribusi Biringkassi PT. Semen Tonasa II Pangkep - A.M Shiddiq Yunus; Herman Nauwir (Jurnal Teknik Mesin Sinergi, 2008)
This research is aimed to determine the chemical compounds and to measure the electrical characteristics of pollutant of polymer 6 KV isolator in distribution station of PT. Semen Tonasa Biringkassi. Research methodology that applied in this study is laboratory experimental which follow several procedural stages: determination of distribution station for taking sample of pollutant then examination of chemical compounds and electrical characteristics of pollutant. The chemical compounds that will be examined are composition of compounds and conductivity of pollutant. Besides, the electrical examination is to measure the surface conductivity of isolator. The result of this study shows that the composition of compounds consists of Zn, Na, Fe and Calcium (Ca). For measurement of pollutant conductivity it is concluded that the higher pollutant’s concentration, the higher value of conductivity. Another result shows that polymer isolator is much more conductive while polluted by pollutant than by kaolin.